(untitled) (Prithvi Journal of Research and Innovation, 2022)
The main objective of this paper is to determine the chemical parameters: pH, optical density (OD), electrical conductivity (EC), percentage of moisture content, total ash, silica, dietary fiber, total acid, vitamin C, total reducing sugar, and formaldehyde content, of selected fruits (apple, banana, coconut, grape, litchi, mango, mousambi, papaya, pineapple, pomegranate and watermelon) available in the markets of Pokhara. Chemical parameters were analyzed by using standard methods in the Research Laboratory of Prithvi Narayan Campus Pokhara, Nepal from 15th March 2022 to 14th June 2022. The pH content ranged from 3.17 to 5.40 indicating acidic nature of all the fruit juices. Electrical conductivity was maximum for coconut juice (818 μS cm–1) followed by pomegranate, grape, mousambi and pineapple whereas that of mango was minimum (246 μS cm–1). Maximum to minimum value of moisture content, total ash, dietary fiber, titratable acidity and vitamin C were from 93.59% (for watermelon) to 72.80% (for coconut), 1.705% (for banana) to 0.360% (for watermelon), 4.52% (for coconut) to 0.35% (for watermelon), 0.098368% (for coconut) to 0.022448% (for watermelon), and 0.049354% (for mousambi) to 0.004121% (for grape) respectively. The highest value for total reducing sugar was recorded in Papaya (2.913269%) whereas lowest value observed in coconut (0.2106619%). Washable formaldehyde content was ranged from 0.01942085% (for grape) to 0.00038287% (for watermelon). The observed chemical parameters of fresh fruits as analyzed by using standard methods are in agreement with previously published values. This study shows that fruit samples are nutritious and fit for fresh eating by consumers.